2018
DOI: 10.1136/annrheumdis-2018-214175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a distinct imaging phenotype may improve the management of palindromic rheumatism

Abstract: ObjectivesTo use high-resolution imaging to characterise palindromic rheumatism (PR) and to compare the imaging pattern observed to that seen in new-onset rheumatoid arthritis (NORA).MethodsUltrasound (US) assessment of synovitis, tenosynovitis and non-synovial extracapsular inflammation (ECI) was performed during and between flares in a prospective treatment-naive PR cohort. MRI of the flaring region was performed where possible. For comparison, the same US assessment was also performed in anticyclic citrulli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 22 publications
2
35
2
Order By: Relevance
“…Isolated extra-capsular inflammation appeared to distinguish PR from RA as this pattern was rarely seen in the RA patients. As may be expected, US inflammation was rarely seen in PR patients when they were not flaring (11).…”
Section: Is Pr Simply Relapsing-remitting Ra?supporting
confidence: 71%
See 3 more Smart Citations
“…Isolated extra-capsular inflammation appeared to distinguish PR from RA as this pattern was rarely seen in the RA patients. As may be expected, US inflammation was rarely seen in PR patients when they were not flaring (11).…”
Section: Is Pr Simply Relapsing-remitting Ra?supporting
confidence: 71%
“…In a cross-sectional analysis of a Spanish PR cohort, the frequency of anti-CCP antibodies was similar in PR compared with early RA patients (53% vs 55% respectively) (6). Other international PR cohorts report similarly high frequencies of anti-CCP positivity (between 46% and 68%) (7)(8)(9)(10)(11). A notable outlier is a recently described Taiwanese PR cohort where only 11/84 (13%) of patients were anti-CCP positive and 12/84 (14%) were RF positive (12).…”
Section: Is Pr Simply Relapsing-remitting Ra?mentioning
confidence: 95%
See 2 more Smart Citations
“…We thank Sanmarti et al 1 for their interest in our recent paper in which we describe the distinct imaging phenotype of palindromic rheumatism (PR) 2. As the authors point out, we identified a high prevalence of ultrasound (US) extra-capsular inflammation in flares of PR, often without coexistent US synovitis.…”
mentioning
confidence: 87%